2013
DOI: 10.1007/s10571-013-9982-z
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Prevents β-Amyloid Neurotoxicity in Primary Cultured Cerebellar Granule Neurons

Abstract: Thymoquinone (TQ), a bioactive constituent of Nigella sativa Linn (N. sativa) has demonstrated several neuropharmacological attributes. In the present study, the neuroprotective properties of TQ were investigated by studying its anti-apoptotic potential to diminish β-amyloid peptide 1-40 sequence (Aβ1-40)-induced neuronal cell death in primary cultured cerebellar granule neurons (CGNs). The effects of TQ against Aβ1-40-induced neurotoxicity, morphological damages, DNA condensation, the generation of reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 56 publications
5
31
0
Order By: Relevance
“…Pre-treatment with TQ is supposed to modulate the NP-SH levels, thereby protecting against As-induced oxidative damage. 29 Similar findings were obtained by Ismail et al (2013) in primary cultured cerebellar granule neurons where TQ prevented β-amyloid induced neurotoxicity. 43 LPO refers to the oxidative degradation of lipids, in which ROS steal electrons from the lipids in cell membrane resulting in cell damage.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Pre-treatment with TQ is supposed to modulate the NP-SH levels, thereby protecting against As-induced oxidative damage. 29 Similar findings were obtained by Ismail et al (2013) in primary cultured cerebellar granule neurons where TQ prevented β-amyloid induced neurotoxicity. 43 LPO refers to the oxidative degradation of lipids, in which ROS steal electrons from the lipids in cell membrane resulting in cell damage.…”
Section: Discussionsupporting
confidence: 72%
“…29 Similar findings were obtained by Ismail et al (2013) in primary cultured cerebellar granule neurons where TQ prevented β-amyloid induced neurotoxicity. 43 LPO refers to the oxidative degradation of lipids, in which ROS steal electrons from the lipids in cell membrane resulting in cell damage. In our study, statistically significant increase in LPO was observed on exposure to different doses of As when compared to control.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies have shown anti‐inflammatory, immunomodulatory, and neuroprotective effects of TQ in different models of neurodegeneration and neurotoxicity such as ischemia, depression, temporal lobe epilepsy, diabetes‐mediated neuropathy, and toluene‐, lead‐, or ethanol‐induced neurotoxicity . Also, TQ has been evaluated as a potential therapeutic agent on cultured neurons . Due to its antiproliferative, chemo‐preventive, cell‐cycle regulatory, and apoptosis‐inducing effects, TQ may be a potential nutraceutical for cancer therapy .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this demonstrate that TQ has the neuroprotective effects against Aβ-induced toxicity in PC 12 cells (Khan, Islam &Vaibhav 2012). TQ may be able to protect cerebellar granule neurons (CGN) from β-amyloid peptide 1-40 sequence (Aβ1-40) toxic effects through the suppression of caspases and lessen the generation of free radicals with a resultant improvement in cell viability (Ismail, Ismail & Mazlan 2013). TQ is also shown to inhibit non-enzymatic peroxidation in cow lysosomial brain phospholipids (Gali-Muhtasib, El-Najjar & Schneider-Stock 2006).…”
Section: Resultsmentioning
confidence: 74%